If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(r + 9) = -27 Reorder the terms: -2(9 + r) = -27 (9 * -2 + r * -2) = -27 (-18 + -2r) = -27 Solving -18 + -2r = -27 Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '18' to each side of the equation. -18 + 18 + -2r = -27 + 18 Combine like terms: -18 + 18 = 0 0 + -2r = -27 + 18 -2r = -27 + 18 Combine like terms: -27 + 18 = -9 -2r = -9 Divide each side by '-2'. r = 4.5 Simplifying r = 4.5
| ((n+1)(n+2)(2n+3))/6 | | x=144p/y | | -10(n+10)=-270 | | 3x+16=180 | | 216-2x=180 | | 4x^2-29x-12=0 | | y+75+3y+5=180 | | 8x-5+3=x-7+10 | | w/12=64 | | 3x+7+5x-35=180 | | 6x+6x=16x-42 | | 12/64 | | (6n+9n^6+13n^5)-(-16n^5+2n^6-5n)= | | 6z-7q=2z+8 | | 2e^5x+3=5 | | 2/9a=2/3 | | 6n+9n^6+13n^5= | | 1/3x+1/4y=12 | | x^3-2x^2-7x+14=0 | | 12y+30=24(3.25)+18 | | k^2-16+225=0 | | 3.7=6.1-0.4x | | -1/5x-3=17 | | 8/4-8=12 | | A+B+B+B+80+90= | | -4.1+-7z=3.6 | | 12-3(2w+1)=7w-3(7w+w) | | 2(x-1)=4x-4 | | 2x+2x-9=11 | | 4=5C-(-14) | | 5t-1=60-5 | | 1/2(-3)+5 |